The multidimensional implications of entrepreneurial orientation on export performance : empirical evidence from manufacturing SMEs in Tanzania - Ringo, Denis Samwel (2023)
Purpose – This study aims to examine the influence of the entrepreneurial orientation (EO) dimensions (innovativeness, risk-taking, proactiveness, competitive aggressiveness and autonomy) on the export performance (EXP) of small and medium enterprises (SMEs). Design/methodology/approach – In this study a cross-sectional survey design was used and data were collected from 250 managers of manufacturing-exporting SMEs in Tanzania. The developed conceptual model was empirically tested using confirmatory factor analysis and hierarchical regression. Findings – The results reveal that innovativeness, risk-taking, competitive aggressiveness and autonomy have a significant positive influence on EXP. However, proactiveness hurts EXP. Additionally, findings indicate that the dimensions of EO do not have an equal impact on SMEs’ EXP. Research limitations/implications – This study only covered SMEs; future studies would be advised to include large firms because they may behave differently with respect EO due to their resource advantages. Furthermore, this study was conducted in a single country, Tanzania, and thus the findings should be interpreted cautiously, since each country has specific institutional frameworks that foster entrepreneurship and entrepreneurial culture in a different way. Originality/value – The context of this study contributes significantly to the research’s originality. The study contributes to the body of knowledge on the EO-EXP link in developing countries, where research on EO-export is scant, and it further contributes to the debate on the EO-EXP link by demonstrating that the dimensions of EO do not have an equal impact on SMEs’ EXP, and accordingly a disaggregated approach would be more meaningful. Furthermore, the study contributes with regards the role of competitive aggressiveness and autonomy in improving SMEs’ EXP, which has received little attention in previous studies.